Allusion and intertext : dynamics of appropriation in Roman poetry - Hinds, Stephen (Roman literature and its contexts, 1998)
The study of the deliberate allusion by one author to the words of a previous author has long been central to Latin philology, which has developed some enviable critical tools for scrutinizing the subtleties of allusive art. However, literary Romanists have been diffident about situating such work within the more spacious inquiries into intertextuality now current - inquiries which find all discourse to be constituted by negotiations between texts, or between other cultural expressions analysable as 'texts'. This book represents a new attempt to find (or recover) some space for the study of allusion - as a project of continuing vitality - within an excitingly enlarged universe of intertexts. It combines traditional classical approaches with modern literary-theoretical ways of thinking, and offers attentive close readings, innovative perspectives on literary history, and theoretical sophistication of argument. Like other volumes in the series it is among the most broadly conceived short books on Roman literature to be published in recent years.